Factor analysis to evaluate the financial performance of the construction industry in an emerging market: The case of Colombia; Análisis factorial para evaluar el rendimiento financiero de la industria de la construcción en un mercado emergente: El caso de Colombia - Judith Vergara; Maribel Serna (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
Factor analysis is a method used to reduce several variables into fewer dimensions called factors. This study conducts factor analysis on the financial ratios of the construction companies in Colombia in the period 2000-2014. According to that, the purpose of the study is to use the factorial analysis technique to determine whether the financial ratios are related to a smaller number of unobservable factors and eliminate redundancy among them. The results show that it is possible to explain 88.753% of the variance with 13 financial ratios grouped into three factors.
Keywords: L74; D21; 330; construction companies; developing countries; factorial analysis; financial ratio analysis